(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2010)
In this article is presented a draft letter of E. Pirajno of Mandralisca (1809-1864) to K. von Estorff (1811-1877). The baron, representative of the antiquarianism in northern Sicily in 19th century, comunicates the drafting of a work about the mintage of Lipara, temporarily delayed by technical impediments. At Lipari Pirajno meanwhile continues the excavations into his land, anciently occupied by the necropolis, where he recovers many archaeological finds. Also the purchased artifacts at Tindari increase his private archaeological collection.